Organizational Justice and Deviant Behaviour: A Systematic Literature Review and Bibliometric Analysis - Rabuni Aiswarya. P; Dr. Syed Khalid (Qubahan Academic Journal)
This research paper conducts a thorough examination of the intricate interplay between deviant behavior and organizational justice over a span of 21 years, employing a systematic literature review and bibliometric analysis based on 33 papers extracted from Scopus. The analysis encompasses trends in publication, influential authors, prominent countries and institutions, key journals, and emerging keywords within the field. Methodologically, data is meticulously extracted and rigorously analyzed. The study reveals dynamic publication trends and highlights influential figures, with countries like the USA and Indonesia taking the lead in research contributions. Notable journals and significant keywords are central to the discourse. The research also identifies limitations in current literature, calling for cross-disciplinary exploration and considerations of moderating factors. Future directions encompass delving into leadership dynamics, organizational culture, and regional/cultural influences.